Sharīʿa in Africa Today Reactions and Responses - Chesworth, John A.; Kogelmann, Franz (Brill, 2020)
Sharīʿa in Africa Today. Reactions and Responses explores how Islamic law has influenced relations between Muslims and Christians, through a series of case studies by young African scholars working in four African countries: in Sudan where total Sharīʿa was applied until recently; in Nigeria where the Northern states re-introduced Sharīʿa courts; in Kenya where the place of Islamic courts has been contested in constitutional debates; in Tanzania where Muslims are calling for the re-introduction of Islamic courts.